ЖОҚАРЫ ОҚЫЎ ОРЫНЛАРЫ ТАЛАБАЛАРЫНДА ДЕНЕ ТӘРБИЯСЫНЫҢ ӘҲМИЙЕТИ - Ережепов, А.; Мамутов, П.Ж. (SCIENCE and SOCIETY, 2018)
The article has a staged character about the necessity of improving the curriculum in the subject "Physical education". The author tries to draw attention to the issue of influence of physical culture on the health of students and the importance of physical culture in professional training of a future specialist. The modest work is abstract in nature and is, undoubtedly, the first step of a future pilot study.
Keywords: sports; life; physical culture; students; active lifestyle